Modeling and Bioinformatics Identify Responders to G-CSF in Patients With Amyotrophic Lateral Sclerosis - Johannesen, Siw; Huie, J. Russell; Budeus, Bettina; Peters, Sebastian; Wirth, Anna M.; Iberl, Sabine; Kammermaier, Tina; Kobor, Ines; Wirkert, Eva; Küspert, Sabrina; Tahedl, Marlene; Grassinger, Jochen; et al. (Frontiers in Neurology, 2021)
Objective To develop an integrative approach using modelling and bioinformatics with various potential biomarkers to treat Amyotrophic Lateral Sclerosis (ALS) patients. Filgrastim (Granulocyte-Colony Stimulating Factor), a hematopoietic growth factor with excellent safety, routinely applied in oncology and stem cell mobilization, had shown preliminary efficacy in ALS. With biomarkers to monitor/predict treatment effects and substantiate a potential role for Filgrastim. Methods We conducted individualized long-term filgrastim treatment of 36 ALS patients. The PRO-ACT database, with outcome data from 23 intl. clinical ALS trials, served as historical control and reference for modelling. Imaging data, cytokines, as well as cellular data from stem cell analysis were processed as biomarkers in non-linear principal component analysis (NLPCA) to identify response. Results Filgrastim was safe, treated patients performed significantly better over PRO-ACT patients in disease progression and survival. Particularly, Cox proportional hazard and matched pairs analyses revealed a significant survival benefit for filgrastim treated patients. Interestingly, strong treatment response to filgrastim with a median survival of 3.8 years was associated with younger age, increased hematopoietic stem cell mobilization, less aggressive inflammatory cytokine plasma profile, and reduced fractional anisotropy as determined by diffusion tensor imaging. Most importantly, non-linear principal component based biomarker analysis revealed individual responses as early as within 3 months of therapy. Conclusion Longtime filgrastim is safe, well tolerated and has positive effects on disease progression and survival. Cytokines, stem cell function, and brain MRI biomarkers identify filgrastim responders among ALS patients, and pave the way to an effective individualized treatment option.